Antibodies to clustered acetylcholine receptor: expanding the phenotype. (21st September 2013) - Devic, P.; Petiot, P.; Simonet, T.; Stojkovic, T.; Delmont, E.; Franques, J.; Magot, A.; Vial, C.; Lagrange, E.; Nicot, A. S.; Risson, V.; Eymard, B.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose To provide a detailed phenotypical description of seronegative patients with generalized myasthenia gravis and antibodies to clustered acetylcholine receptors (AChRs) and to assess their frequency amongst a French seronegative generalized myasthenia gravis (SNMG) population. Methods A French SNMG database was created and the sera from the 37 patients included in it were analysed by immunofluorescence of cell‐based assays using cotransfection of AChR subunit genes together with rapsyn to densely cluster the AChRs. Results Sixteen per cent (n = 6) of the SNMG patients were found to have antibodies to clustered AChR. They presented either with early onset MG and thymic hyperplasia, late onset MG and thymic involution, or thymoma associated MG. They responded well to cholinesterase inhibitors and immunosuppressants. Conclusions Patients with antibodies to clustered AChR account for a significant proportion of SNMG patients and resemble patients with AChR antibodies detected by standard radio‐immunoprecipitation.